Micropropagation of an orchid Dendrobium strongylanthum Rchb.f. - Kong, Q.; Yuan, S. Y.; Végvári, Gy. (International Journal of Horticultural Science, 2007)
A simple and reliable procedure for in vitro propagation of an orchid Dendrobium strongylanthum Rchb.f. was studied. Protochorm was induced from seed explants on 1/2 MS medium supplemented with 0.2 mg/L NAA. A mass of protochorm could be multiplied on proliferated medium of 1/2 Ms containing 0.5 mg/L V-6-BA. And bud differentiation of green global body was cultured in the same media, 2-2.5 cm shoots were formed after 30 day of culture. Addition of mashed banana and 0.5 mg/L NAA to 1/2 MS medium promoted root formation and vigorous growth. The plantlets were acclimatized and transplanted to compound materials of humus:sawdust (1:1) in greenhouse, the survival rate was more than 98%.